Viktor Balabin. Theoretical and concertual framework for military translation - Viktor Balabin (Philological Treatises, 2020)
The special theories of translation studies lack a scientifically substantiated theory of military translation, which should be based on scholarly, linguistic and translatological grounds, meet the established methodological and scholarly eligibility criteria, declare its own object, subject, research tasks, theoretical models and conceptual construct. The theory of military translation is a branch of translation studies special theories. It can be defined as a group of well-profiled, structured and summarized scholarly facts, theoretical judgments, hypotheses and methodological provisions, which are coherently integrated into a system by carefully selected and terminologically refined units of its conceptual construct, which reveal the essence and specificity of the military interpreter’s professional duties. The object of the military translation theory encompasses not only the traditional sphere of translation and interpreting, but also the entire sphere of the linguistic support of forces.